Struktur Bawah Permukaan Intrusi Batuan Beku Di Parangtritis, Pantai Selatan Yogyakarta Ditinjau Dari Data Anomali Medan Gravitasi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Gravitational field investigation which covers 10.5 km2 area has been carried out at Parangtritis. The purposes of this investigation are to apply methods and concepts of gravity anomaly analysis and to estimate the mass distribution of the igneous rock intrusion. La Coste & Romberg Gravity Meter model G-1118 with MVR Feedback System that has 0.005 miligals accuracy is used to measure the gravity. GPS with two Trimble Navigation 4600 LS Geodetic System Surveyor Single Frequency is used to determine the position. Complete Bouguer anomaly at irregular surface has been yielded after rigorous reduction of the observed data. Projections of the data to a regular surface is processed by Taylor's series approximation methods. Local and regional Bouguer anomalies are separated by upward continuation method which has been tested using synthetic data or model. Quantitative interpretation of local Bouguer anomaly using 2.5-D method of Talwani et aI. yields mass distribution with density of 2.9 gr/cm3. It is interpreted as igneous rocks intrusion i.e., diorite and andesite. The distribution of mass has strike length to the north-west of 1.5 km and to the south-east of 1 km.